Polycyclic aromatic hydrocarbons removal from produced water by electrochemical process optimization - Yaqub, A. (De Gruyter Open Ltd, 2017)
Produced water is actually the wastewater separated from petroleum crude oil. Electrochemical-oxidation experiments was conducted for degradation of 16 priority polycyclic aromatic hydrocarbons (PAHs) using DSA type Ti/IrO2 anode. Laboratory scale batch reactor was used for degradation studies. To get the maximum PAHs removal electrochemical process optimized on three independent variable current density, pH and electrolysis time. The response surface modelling (RSM) based on a Box-Behnken design was applied to get appropriate experimental design. X1, X2 and X3 are the coded factors of independent variables such as the current density, pH and electrolysis time, respectively. Maximum removal was 95.29 at optimized conditions such as current density of 9 mA/cm2, pH 3 and electrolysis time 3.7 h. Quadratic model was suggested best fit model. The results of the Analysis of Variances (ANOVA) for PAHs demonstrated that the model was highly significant. © 2017 Asim Yaqub et al., published by De Gruyter Open 2017.